Precalculus: Mathematics for Calculus, 7th Edition

Published by Brooks Cole
ISBN 10: 1305071751
ISBN 13: 978-1-30507-175-9

Chapter 1 - Review - Exercises: 45

Answer

$\dfrac{2}{x}+\dfrac{1}{x-2}+\dfrac{3}{(x-2)^{2}}=\dfrac{3x^{2}-7x+8}{x(x-2)^{2}}$

Work Step by Step

$\dfrac{2}{x}+\dfrac{1}{x-2}+\dfrac{3}{(x-2)^{2}}$ Evaluate the sum of the three rational expressions using their LCD (Least common denominator) and simplify if possible: $\dfrac{2}{x}+\dfrac{1}{x-2}+\dfrac{3}{(x-2)^{2}}=\dfrac{2(x-2)^{2}+x(x-2)+3x}{x(x-2)^{2}}=...$ $...=\dfrac{2(x^{2}-4x+4)+x^{2}-2x+3x}{x(x-2)^{2}}=...$ $...=\dfrac{2x^{2}-8x+8+x^{2}-2x+3x}{x(x-2)^{2}}=\dfrac{3x^{2}-7x+8}{x(x-2)^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.